2012
DOI: 10.1111/j.1742-1241.2011.02886.x
|View full text |Cite
|
Sign up to set email alerts
|

Autologous stem cell therapy in the treatment of limb ischaemia induced chronic tissue ulcers of diabetic foot patients

Abstract: The transplantation of BMCs as well as TRCs proved to be safe and feasible. Improvements of microcirculation and complete wound healing were observed in the transplant groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
102
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(106 citation statements)
references
References 30 publications
1
102
0
3
Order By: Relevance
“…Following careful screening of titles and abstracts, 399 articles were excluded leaving 7 articles that fulfilled the predefined inclusion criteria and were included in the final analysis [20][21][22][23][24][25][26]. A total of 6 publications were full-text articles out the 7 studies [20,[22][23][24][25][26], whereas 1 publication was a meeting conference [21].…”
Section: Study Selectionmentioning
confidence: 99%
“…Following careful screening of titles and abstracts, 399 articles were excluded leaving 7 articles that fulfilled the predefined inclusion criteria and were included in the final analysis [20][21][22][23][24][25][26]. A total of 6 publications were full-text articles out the 7 studies [20,[22][23][24][25][26], whereas 1 publication was a meeting conference [21].…”
Section: Study Selectionmentioning
confidence: 99%
“…Recent studies have outlined some successful approaches to promoting wound healing with MSCs, including autologous bone marrow-derived MSCs in fibrin matrix 52 or, more recently, intramuscular injection of autologous MSCs to improve diabetic wound closure. 54 While some trials have been aimed primarily at safety of MSC use for wound healing, 50 several clinical trials have shown the potential benefit of MSCs for inclusion in wound healing devices, including improved average rate of wound healing and general limb perfusion after treatment 53 and also improved acute wound healing correlating to the number of injected cells. 52 Despite any effects on healing, there was some doubt as to any reduction in limb amputation rate or relative pain levels among groups, a major consideration for effective therapy in chronic wounds.…”
Section: Chronic Skin Woundsmentioning
confidence: 99%
“…In support, recent studies confirmed the clinical improvement in patients with severe limb ischemia following intramuscular administration of BM-MNCs in terms of lower amputation rates and improved ankle-brachial index [77][78][79]. In contrast, a small randomized trial reported non-significant trends toward improved ankle brachial index, and wound healing in patients treated with BM-MNC [80].…”
Section: Therapeutic Utility Of Bm-mncs In CLImentioning
confidence: 75%